RNA Interference in Trypanosoma brucei role of the n-terminal RGG domain and the polyribosome association of argonaute - Shi, H.; Chamond, N.; Djikeng, Appolinaire; Tschudi, C.; Ullu, E. (Elsevier, 2009)
Argonaute proteins (AGOs) are central to RNA interference (RNAi) and related silencing pathways. At the core of the RNAi pathway in the ancient parasitic eukaryote Trypanosoma brucei is a single Argonaute protein, TbAGO1, with an established role in the destruction of potentially harmful retroposon transcripts. One notable feature of TbAGO1 is that a fraction sediments with polyribosomes, and this association is facilitated by an arginine/glycine-rich domain (RGG domain) at the N terminus of the protein. Here we report that reducing the size of the RGG domain and, in particular, mutating all arginine residues severely reduced the association of TbAGO1 with polyribosomes and RNAi-induced cleavage of mRNA. However, these mutations did not change the cellular localization of Argonaute and did not affect the accumulation of single-stranded siRNAs, an essential step in the activation of the RNA-induced silencing complex. We further show that mRNA on polyribosomes can be targeted for degradation, although this alliance is not a pre-requisite. Finally, sequestering tubulin mRNAs from translation with antisense morpholino oligonucleotides reduced the RNAi response indicating that mRNAs not engaged in translation may be less accessible to the RNAi machinery. We conclude that the association of the RNAi machinery and target mRNA on polyribosomes promotes an efficient RNAi response. This mechanism may represent an ancient adaptation to ensure that retroposon transcripts are efficiently destroyed, if they become associated with the translational apparatus.